Highly selective adsorption for palladium removal by impregnation preparation of a macroporous N-based functional composite. Issue 1 (2nd January 2018) - Lu, Yanchao; Xu, Lei; Li, Yanli; Yang, Hua; Liu, Ziyang; Jiang, Li; Zhang, Anyun
ABSTRACT: A novel mesoporous polymer-based composite, C7-BTBP/XAD-7, was prepared by impregnating 6, 6'-bis(5, 6-diheptyl-1, 2, 4-triazin-3-yl)-2, 2'-bipyridine (C7-BTBP) into the pores of the polymeric XAD-7 carrier. The microstructure of the material was characterized by scanning electron microscopy (SEM), nitrogen adsorption-desorption isotherms, and thermogravimetric analysis (TGA). The selective adsorption of Pd(II) onto C7-BTBP/XAD-7 from a HNO3 medium containing some typical metals, including Ru(III), Fe(III), Mo(VI), Zr(IV), Li(I), Na(I), K(I), Rb(I), Cs(I), Mg(II), Ca(II), Sr(II), Ba(II), Y(III), La(III), Nd(III), and Yb(III), was investigated. The polymeric composite exhibited strong adsorption affinity, high selectivity, and fast adsorption rate for Pd(II) in 3.0 M HNO3 . The adsorption isotherm fitted well with Langmuir model, with a maximum adsorption capacity of 0.412 mmol/g. The hybrid polymeric composite was very stable in HNO3 solution. The kinetics of Pd(II) coordinated with C7-BTBP was discussed by Density Function Theory (DFT) calculations.